Customer Satisfaction and Role of Channel Intermediaries In Life Insurance Services: A Comparative Study - Rajeev K Shukla; Pradeep Bhatt and Sharad Shrivastava (Abhigyan, 2012)
In technical term Life Insurance is a contract providing for payment of a sum of money to the person assured. Life insurance provides an opportunity to protect from personal risk exposures like repayment of debts after death, providing for a surviving spouse and children, fulfilling other economic goals, leaving a charitable legacy. The present study was intended to get insight on role of channel intermediaries in customer satisfaction in life insurance services. Findings of the study revealed that Channel intermediaries in Life Insurance services play an important role in customer satisfaction. Different channel intermediaries have their own unique importance in way of delivering life insurance services, as the role of these intermediaries are different in nature and perform their operation in different manner. The study revealed that Channel wise there is significant difference in customers’ satisfaction towards Error Free Services provided by channel intermediaries, Service provided on Time, Processing Fee charged, Uniqueness in Service offerings and After Sales Services provided by different channel intermediaries of Life Insurance services